Study on solidification properties of chemically bonded phosphate ceramics for cesium radionuclides. Issue 10 (July 2020) - Tao, Yan; Zhenyu, Lai; Chunrong, Ren; Yuanyuan, Wang; Zhichao, Hu; Xin, He; Jie, Wu; Mengliang, Liu; Qiubai, Deng; Khan, Khalid; Zhongyuan, Lu; Shuzhen, Lv
Abstract: Chemically bonded phosphate ceramics (CBPC) are prepared by the acid-base neutralization reaction of MgO and KH2 PO4, which has a wide application prospect in the field of solidifying high-level liquid wastes and heavy metals. Herein, the effect of Cs + on the solidifying process of the CBPC matrix with different M/Ps is studied through the change in pH values of the hydration process, the microstructure, and the phase composition of hydration products, as well as the compressive strength and leaching rate of the solidified form. The results show that with the increase in the Cs + content, although the initial compressive strength of the solidified form with the M/P ratio in the range of 6:1 to 10:1 decreases, the compressive strength of the specimens reached 7 MPa after curing for 6 h, which was suitable for the rapid emergency treatment of Cs-containing wastes. Cs + participates in the hydration reaction of the CBPC matrix but does not change the type of hydration products. With the addition of Cs +, the microstructure of hydration products changes from dense prismatic crystals to loose and porous cluster-like materials. The existing forms of Cs + in the CBPC matrix are MgCsx K1-x PO4 ·6H2 O and Cs3 PO4 . Generally, CBPC solidified form has an excellent solidification performance on Cs + ; the normalized leaching rate of Cs + in CBPC solidified form is in the range of 1.3127·10 −6 ~ 9.1362·10 −6  g/(m 2 ·d), and the effective solidification rate is more than 99.136%.